TO THE ISSUE OF ICT INTEGRATION INTO THE EDUCATIONAL PROCESS AND THEIR USE IN NON-FORMAL EDUCATION - Shalova, Natalia; Khymai, Nataliia; Zarivna, Oksana (Sworld-Us Conference proceedings, 2023)
The main problems related to the integration of ICT into educational process are considered. The advantages and disadvantages of ICT integration are indicated. It is emphasized that it is necessary for teachers to master ICT in full for the successful use